Mutuality of being in the batak toba community: exploring the maingain tradition in the modern era - Aldi Pahal Rizky Sihaloho (Institute for Advanced Science, Social, and Sustainable Future, 2023)
This paper explains mutuality of being that is seen through the tradition of mangain (adopts a child) in Batak Toba society which has progressed over time. This tradition is familiar for the Batak Toba people who want to do mixed marriage with non-Batak ethnic groups. In the reality, the whole function of mangain is rooted on ‘child adoption’. This tradition directs people who receive a Batak Toba clan—I called it the “Orang Batak baru”—, not only Batak Toba people, to a Dalihan Na Tolu life which is mutually dependent on each other. On the other hand, mangain does not encourage them forget their parents who gave birth to, and nurturanced for, them. Mangain has become an example of a tradition that can strengthen the unity of Indonesia, a plural country, because kinship in here is not only seen from procreation. Diversity has been seen as a source of conflict of interest between groups in Indonesia. The final result of this article showed that mangain tradition accommodates the Batak Toba people love non-Batak people, and vice versa, which can be seen from the implications of the mutuality of being in it. Archival data, writing of academics from various fields up to other forms of writing, became the basis of this research. Interviews of informants who have been directly involved in the mangain process, even wrote it in a book, then completed this paper.